Foreign exchange premia and non-neutrality to monetary policy in general equilibrium models - Clarete, Ramon L. (Journal of International Economics)
We present a simple monetized extension of a traditional small-country, real-side, general equilibrium trade model in which premia on foreign exchange occur, with the value of the quota and the quota premium endogenously determined. Monetary policy is non-neutral in the model, and has real effects, illustrated using a small open economy general equilibrium model of the Philippines, which includes foreign exchange premia. The results emphasize the importance of incorporating domestic monetary policy, fixed exchange rates and associated foreign exchange premia when analyzing the trade policy regime in such a country.